Computational modelling of GPCR signalling dynamics - Ladds, Graham (Henry Stewart Talks, 2020)
GPCRs signalling kinetics can be model using simple equations, Link between computational modelling and pharmacology, Yeast are excellent system for computational models, RGS proteins show non-intuitive activity, Kinetic models of GPCRs can model agonist bias